2018
DOI: 10.1002/eap.1713
|View full text |Cite
|
Sign up to set email alerts
|

Complementary crops and landscape features sustain wild bee communities

Abstract: Wild bees, which are important for commercial pollination, depend on floral and nesting resources both at farms and in the surrounding landscape. Mass-flowering crops are only in bloom for a few weeks and unable to support bee populations that persist throughout the year. Farm fields and orchards that flower in succession potentially can extend the availability of floral resources for pollinators. However, it is unclear whether the same bee species or genera will forage from one crop to the next, which bees sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 103 publications
(203 reference statements)
0
41
0
Order By: Relevance
“…, Martins et al. , Drummond ). However, our results also suggest that flowering crops immediately adjacent to L. maackii flowers are less adequately pollinated.…”
Section: Discussionmentioning
confidence: 99%
“…, Martins et al. , Drummond ). However, our results also suggest that flowering crops immediately adjacent to L. maackii flowers are less adequately pollinated.…”
Section: Discussionmentioning
confidence: 99%
“…, Sardiñas and Kremen , Martins et al. ). When the species‐specific studies are taken together, it is clear that there may be significant interspecific diversity in solitary bee nest site preferences with regard to key environmental characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Quebec, Canada, showed that bee diversity in apple orchards and blueberry and raspberry fields was influenced by the presence of suitable nesting resources (Martins et al. ). Again, the important characteristics of the nesting resource vary, but the availability of bare ground (Potts et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations